Bevacizumab and Sorafenib Modulate P-Glycoprotein Function In Vitro and Bevacizumab Increases In Vivo Sorafenib Plasma Concentrations in Mice - Tandia, Mahamadou; Abbara, Chadi; Noel-Hudson, Marie-Sophie; Amor, Dora; Polrot, Mélanie; Gonin, Patrick; Bonhomme-Faivre, Laurence (International Journal of Innovative Research in Medical Science, 2020)
Overexpression of P-glycoprotein (P-gp) is associated with multidrug resistance. Since sorafenib (NEXAVAR®) is a P-gp (an efflux protein of ATP-binding cassette family) substrate, we tested whether bevacizumab (AVASTIN®), a monoclonal antibody directed toward VEGF (Vascular Endothelial Growth Factor) and sorafenib could modulate P-gp functionality. In vitro two human ovarian carcinoma cells (IGROV1) overexpressing or weakly expressing P-gp were used. Bevacizumab and sorafenib effects on P-gp functionality were evaluated by measuring doxorubicin intracellular accumulation. In vivo study was to document whether bevacizumab could modify sorafenib disposition in mice. Therefore, concentrations of sorafenib were determined by HPLC in plasma of mice bearing a human colorectal carcinoma xenograft when sorafenib is given orally (5 mg/kg) on day 4, alone or after a pretreatment with bevacizumab (5 mg/kg IP) on days 1 and 3. In vitro a significant doxorubicin accumulation and reversion of doxorubicin resistance in P-gp expressing cell lines were observed with bevacizumab or sorafenib pretreatment In vivo, sorafenib AUC was 1.44 fold significantly higher in bevacizumab pretreated group and Cmax was 1.35 fold higher in bevacizumab-pretreated group. Mean residence time of sorafenib increased in the presence of bevacizumab, this increase reflects an improvement of sorafenib bioavailability after bevacizumab pretreatment. We may conclude that bevacizumab pretreatment decreases P-gp functionality and increases doxorubicin intracellular accumulation in vitro and sorafenib plasma concentrations in vivo.